Customer Risk Aversion and Attitude as Predictors of Smartphone Brand Loyalty - Hadibrata, Damar Buana; Wijaya, Angga Pandu (Research Horizon, 2025)
Brand loyalty is crucial in the highly competitive smartphone market, where consumer preferences rapidly evolve. There are still not many studies that link brand loyalty to consumer risk aversion, so further research is needed. This study aims to examine the effect of risk aversion and customer attitudes on brand loyalty, with brand trust as a mediating factor, among Samsung smartphone users in Semarang, Indonesia. A quantitative approach was employed, collecting survey data from 217 respondents using purposive sampling. The data that has been obtained is analyzed using SmartPLS 4.1. The results of the study show that risk aversion, customer attitude, and brand trust have a positive and significant effect on brand loyalty. In addition, risk aversion and customer attitude have been proven to have an effect on brand loyalty through brand trust. These findings underscore the critical role of brand trust in fostering loyalty. Smartphone companies should prioritize trust-building strategies, such as consistent quality, reliable after-sales service, and interactive social media engagement, to enhance consumer loyalty.